Strategi Pengembangan Usaha Fermentasi Biji Kakao Di Kecamatan Juli Kabupaten Bireuen Provinsi Aceh (Studi Kasus Koperasi Perkebunan Kakao Bireuen) - Waliyatul Hamimiy; Mujiburrahmad Mujiburrahmad; Elly Susanti (Fakultas Pertanian, Universitas Syiah Kuala, 2022)
The purpose of this study was to determine the strategy for developing a cocoa fermentation business in a been cocoa plantation cooperative, to analyze internal and external factors that were influenced by a been cocoa plantation cooperative. Strenght, Weakness, Opportunity, and Threat (SWOT) analysis was conducted to formulate an integrated alternative strategy. The QSPM method is then used to evaluate the strategy. The results showed that the position and development of the bireuen cocoa plantation cooperative were in quadrant 5 (Hold and Mountain strategy), which means that the bireuen cocoa plantation cooperative implemented a strategy of market penetration and product development. From the SWOT analysis, the results of alternative marketing strategies that will be carried out in bireuen plantation cooperatives include 1) S-O strategy, namely maintaining cooperative relationships between institutions and maintining physical quality and product taste quality at a reasonable prince 2) W-O strategy, namely collaborating with financial institutions to additional business capital 3) S-T strategy, namely maintaining the quality of human resources in the face of increasingly fierce competition 4) W-T strategy, namely increasing production income to get good quality seeds